Feasibility and safety of intrathecal transplantation of autologous bone marrow mesenchymal stem cells in horses - Maia, Leandro [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP]; Taffarel, Marilda Onghero; Moraes, Carolina Nogueira de [UNESP]; Machado, Gisele Fabrino [UNESP]; Melo, Guilherme Dias [UNESP]; Amorim, Rogério Martins [UNESP] (Biomed Central Ltd, 2015)
Background: Recent studies have demonstrated numerous biological properties of mesenchymal stem cells and their potential application in treating complex diseases or injuries to tissues that have difficulty regenerating, such as those affecting the central and peripheral nervous system. Thus, therapies that use mesenchymal stem cells are promising because of their high capacity for self-regeneration, their low immunogenicity, and their paracrine, anti-inflammatory, immunomodulatory, anti-apoptotic and neuroprotective effects. In this context, the purpose of this study was to evaluate the feasibility and safety of intrathecal transplantation of bone marrow-derived mesenchymal stem cells in horses, for future application in the treatment of neurological diseases.Results: During the neurological evaluations, no clinical signs were observed that were related to brain and/or spinal cord injury of the animals from the control group or the treated group. The hematological and cerebrospinal fluid results from day 1 and day 6 showed no significant differences (P > 0.05) between the treated group and the control group. Additionally, analysis of the expression of matrix metalloproteinase (MMP) -2 and -9 in the cerebrospinal fluid revealed only the presence of pro-MMP-2 (latent), with no significant difference (P > 0.05) between the studied groups.Conclusions: The results of the present study support the hypothesis of the feasibility and safety of intrathecal transplantation of autologous bone marrow-derived mesenchymal stem cells, indicating that it is a promising pathway for cell delivery for the treatment of neurological disorders in horses.
Keywords: Mesenchymal stem cells; Transplantation; Horse; Matrix metalloproteinases; Neurology